Synthesis of 3-Cyano-21-Nitro-N-Confused Porphyrin Derivatives by Isoamyl Nitrite - Zhang, Shaowei; Fu, Xinliang; Ren, Demin; Li, Xiaofang; Yang, Leilei; Yu, Xianyong (Journal of chemical research, 2017)
The 3-cyano-21-nitro-N-confused porphyrin derivatives were synthesised by the nitration reaction of 3-cyano-N-confused-porphyrin with isoamyl nitrite at room temperature in moderate yield. The reaction took placed regioselectively in 21-position carbon of inverted pyrrole of N-confused porphyrins.